Controlling light localization and light-matter interactions with nanoplasmonics. - Giannini,V; Fernández-Domínguez,AI; Sonnefraud,Y; Roschuk,T; Fernández-García,R; Maier,SA (Small, 2010)
Nanoplasmonics is the emerging research field that studies light-matter interactions mediated by resonant excitations of surface plasmons in metallic nanostructures. It allows the manipulation of the flow of light and its interaction with matter at the nanoscale (10(-9) m). One of the most promising characteristics of plasmonic resonances is that they occur at frequencies corresponding to typical electronic excitations in matter. This leads to the appearance of strong interactions between localized surface plasmons and light emitters (such as molecules, dyes, or quantum dots) placed in the vicinity of metals. Recent advances in nanofabrication and the development of novel concepts in theoretical nanophotonics have opened the way to the design of structures aimed to reduce the lifetime and enhance the decay rate and quantum efficiency of available emitters. In this article, some of the most relevant experimental and theoretical achievements accomplished over the last several years are presented and analyzed.